2022
DOI: 10.3390/diagnostics12020354
|View full text |Cite
|
Sign up to set email alerts
|

Incidental CT Findings in the Elderly with Low-Energy Falls: Prevalence and Implications

Abstract: Background: Computed tomography (CT) is commonly used in trauma care, with increasing implementation during the emergency work-up of elderly patients with low-energy falls (LEF). The prevalence of incidental findings (IFs) resulting from CT imaging and requiring down-stream actions in this patient cohort is unknown. We have investigated the prevalence and urgency of IFs from emergency CT examinations in these patients. Methods: A total of 2871 patients with LEF and emergency CT examinations were consecutively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Consistent with our data, incidental findings in whole-body CT scans for severely injured patients are very prevalent [ 9 , 10 ]. However, the overall rate of incidental findings in trauma patients in this present study was considerably lower compared to other published literature (up to 75%) [ 7 , 9 - 12 ]. There were factors such as age, type of trauma, and type of CT that may be the reason for the lower rate.…”
Section: Discussioncontrasting
confidence: 86%
“…Consistent with our data, incidental findings in whole-body CT scans for severely injured patients are very prevalent [ 9 , 10 ]. However, the overall rate of incidental findings in trauma patients in this present study was considerably lower compared to other published literature (up to 75%) [ 7 , 9 - 12 ]. There were factors such as age, type of trauma, and type of CT that may be the reason for the lower rate.…”
Section: Discussioncontrasting
confidence: 86%
“…Also, in 28 (93.3%) of the 30 patients, the incidental finding did not lead to an immediate alteration in clinical management. Other studies have reported a range of incidental findings [35][36][37]. For instance, a study by Niedermeier et al found incidental findings in 73.9% of the patients receiving a CT scan as part of the emergency work-up of elderly patients with low-energy falls [36].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported a range of incidental findings [35][36][37]. For instance, a study by Niedermeier et al found incidental findings in 73.9% of the patients receiving a CT scan as part of the emergency work-up of elderly patients with low-energy falls [36]. Incidental findings were most often discovered with a CT head, CT chest, and CT abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…2 Another study on elderly patients with low-energy falls showed that in CT examinations, 74% of patients had incidental findings. 3 The significance of these missed incidental findings is that if a disease entity remains undetected and unmanaged, disease can progress, and patient outcomes can worsen.…”
Section: Introductionmentioning
confidence: 99%
“…Emergency patients receiving CT scans were reported to have incidental findings in one third of cases but only 9.8% were reported to patients in discharge paperwork 2 . Another study on elderly patients with low-energy falls showed that in CT examinations, 74% of patients had incidental findings 3 . The significance of these missed incidental findings is that if a disease entity remains undetected and unmanaged, disease can progress, and patient outcomes can worsen.…”
Section: Introductionmentioning
confidence: 99%